PENERAPAN PRINSIP RESILIENCE ARCHITECTURE PADA HUNIAN SEMENTARA PASCABENCANA - Jihan Adha Hillal Rois; Fairuz Mutia (Universitas Katolik Soegijapranata, 2022)
AbstractThe number of disasters in the last ten has only increased. However, this condition is not accompanied by a responsive government attitude to take steps to mitigate disasters. Temporary shelters as the government's efforts to deal with disasters in the field of rehabilitation and reconstruction only focus on the speed of development. Resilience architecture does not only focus on aspects of speed and accuracy of construction but also on aspects of sustainability to achieve a balance between economic, social and community regenerative growth through architectural design. This study aims to determine the extent to which the principles of resilience architecture are applied in the design of post-disaster housing, by analyzing the application of the concept of resilience architecture in the aspects of Efficiency and Effectiveness, Economical, Eco-tech and Sustainability, Durability, Flexibility. The research method used is Dynamic Mixed Methods with the Paired Comparison Rating Scale analysis approach by measuring and comparing several samples that meet the number of indicator items made. The results of research on several objects show that temporary housing is limited in responding to the aspects of accuracy, speed, and technology of the construction system, but in terms of environmental sustainability it still has not shown optimal results.Keywords: Construction, Local-Oriented Design, Resilience architecture, Temporary Shelters AbstrakJumlah bencana dalam sepuluh terakhir semakin meningkat. Namun, kondisi tersebut tidak dibarengi dengan sikap pemerintah yang tanggap untuk mengambil langkah penanggulangan dalam kebencanaan. Hunian sementara sebagai upaya pemerintah dalam menanggulangi bencana di bidang rehabilitasi dan rekonstruksi hanya berfokus pada kecepatan pembangunan. Resilience architecture tidak hanya berfokus pada aspek kecepatan dan ketepatan konstruksi namun juga pada aspek keberlanjutan untuk mewujudkan keseimbangan antara pertumbuhan ekonomi, sosial, dan regeneratif komunitas melalui desain arsitektur. Penelitian ini bertujuan untuk mengetahui sejauh mana prinsip resilience architecture diterapkan dalam perancangan hunian pascabencana, dengan menganalisis penerapan konsep resilience architecture pada aspek Efficiency and Effectivity, Ekonomis, Eco-tech and Sustainability, Durability, Flexibility. Metode penelitian yang digunakan adalah Dynamic Mixed Methods dengan pendekatan analisis Paired Comparison Rating Scale dengan cara mengukur dan membandingkan beberapa sampel yang memenuhi jumlah butir indikator yang dibuat. Hasil penelitian pada beberapa objek menunjukkan hunian sementara terbatas merespons pada aspek ketepatan, kecepatan, dan teknologi sistem konstruksinya, namun dalam aspek keberlanjutan lingkungan masih belum menunjukkan hasil yang optimal.Kata kunci: Hunian Sementara, Konstruksi, Local-oriented design, Resilience architecture